Cause of death in patients attending multiple sclerosis clinics. - Sadovnick, A; Eisen, K; Ebers, G; Paty, D (1991)
Between 1972 and 1988, 145 deaths occurred among 3,126 patients attending the Multiple Sclerosis (MS) Clinics in Vancouver, British Columbia (N = 1,583), and London, Ontario (N = 1,543). We could determine the exact cause of death in 82.1% of cases (119 of 145). Of the 119 patients for whom the cause of death was known, 56 deaths (47.1%) were directly attributed to complications of MS. Of the remaining 63 deaths, 18 (28.6%) were suicides, 19 (30.2%) were due to malignancy, 13 (20.6%) to an acute myocardial infarction, seven (11.1%) to stroke, and the remainder (9.5%) to miscellaneous causes, of which two may have been suicides. The proportion of suicides among MS deaths was 7.5 times that for the age-matched general population, and the proportion of MS deaths from malignancy was 0.67 times that for the age-matched general population. The proportion of deaths due to malignancy and stroke was the same for the MS patients and the age-matched general population.